Representasi Nasionalisme dan Implementasi Profil Pelajar Pancasila pada Film “Susi Susanti - Love All” dalam Perspektif Semiotika Roland Barthes - Rika Ayu Perdana (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
Film is a means of communication in which elements of language are created. It is on this basis that this study seeks to examine the semiotic aspects of the representation of nationalism and the implementation of the Pancasila Student Profile in the film entitled "Susi Susanti – Love All". This research was conducted using a qualitative-descriptive method using the point of view used by Roland Barthes. The units of analysis are words (dialogue), images (symbols), and sound. This study concludes that the representation of nationalism and the Pancasila Student Profile in the film being analyzed can be seen through the dialogues of the actors, film scenes, and the images and symbols in the film. This aspect can be seen as the meaning of the film which is connotative, denotative, or mythical in nature. 2) Presentation can be done verbally or non-verbally. There are several dialogues that reflect the implementation of the Pancasila Student Profile.